Experimental Characterization And Performance Of Dynamic Vibration Absorber With Tunable Piecewise-Linear Stiffness - Ramlan, Roszaidi; Mustaffer, Muhammad Harith; Abdul Rahman, Mohd Nazim; Putra, Azma (Springer, 2020)
Dynamic vibration absorber (DVA) is one of the ways to control the level of vibration. Among many mechanisms and control strategies of the DVA, passively tuned DVA emerges as one of the most efective absorbers due to its simple mechanism. However, the performance of the passive tuned DVA sufers from narrow suppression bandwidth. This paper introduces a nonlinear dynamic vibration absorber (NDVA) with an adjustable piecewise-linear stifness mechanism which has a characteristic almost similar to hardening stifness to broaden the vibration suppression bandwidth. The mechanism is made of a cantilever beam constrained by two vertically and horizontally adjustable limit blocks on either side of the beam’s equilibrium position. The static and dynamic properties of the proposed NDVA were frst investigated for diferent positions of the limit blocks. Then the performance of the NDVA was compared with the linear DVA in terms of the vibration suppression bandwidth, separation of resonance frequencies and the ability to cope with mistuning. Overall, the NDVA seems to outperform the linear DVA, and it is more forgiving in the case of mistuning.